PERANCANGAN BUKU CERITA BERGAMBAR BERJUDUL ”ASAL-USUL TARI RONGGENG IBING” UNTUK REMAJA BERUSIA 13-17 TAHUN - Martinus Eko Prasetyo; Febbri Irawan Yusuf; Asrullah Ahmad (Universitas Trisakti, 2023)
Design of a Picture Storybook titled “Origins of the Ronggeng Ibing Dance” for Youth 13-17 Years Old. The Ronggeng Ibing dance is a type of ronggeng art known in the Sundanese community that has developed in the southeastern part of West Java, especially in Ciamis Regency, Banjar City, and Pangandaran Regency. In this Ronggeng Ibing, several female dancers are accompanied by Sundanese gamelan and kawih-kawih (singing) music. Sundanese kawih-kawih as accompaniment to the Sundanese Ibing dance also experienced development with many new kawih-kawih being created. The research method was carried out by conducting interviews with resource persons, distributing questionnaires, and collecting and reading literature. The result of this design is in the form of an illustrated storybook that will discuss the origins of the Ronggeng Ibing Dance. Through this design, it is hoped that it can provide insight to children about their origins more specifically in terms of dance culture, can increase children's reading interest, and can make it easier for children to understand cultureKeywords: storybook, ronggeng ibing, Pangandaran Regency, West Java